Kesiapan Sumberdaya Manusia Ketenaga Kerjaan Indonesia di Era Masyarakat Ekonomi ASEAN (MEA) - Aminah, Sitti (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2016)
The aims of the study was to describe the potential and human resource capacity of Indonesian workers in the era of the ASEAN Economic Community (AEC). Quantitative descriptive approach is used to answer the aims of study with displaying the secondary data. The results of this study showed that Indonesia has the potential in the aspects largest of area and rich of natural resources, population and gross domestic product that can contribute to the economy of ASEAN. Indonesia is facing problem lack to level of productivity and labor cost. To increase the capacity of the workforce, the goverment must be formulated policies: providing incentives for non-university graduated to continue their education, increasing the number of vocational high school graduated with international competency certification, the revitalization of vocational training centers and increase the role of university-industry.